Second Five year Plan Kerala Review of the Progress of Schemes - Planning Commission (Planning Commission, 1956)
Kerala State in its present form emerged from the scheme of States Reorganisation that took place in November 1956. the new State was constituted from the old Travancore-Cochin State, short of the Tamil speaking southern Taluks of the present Kanyakumari District of Madras and with the Malabar area of the former Madras State added on to it. By the time the Kerala State was born, the Second Five Year Plan had already been finalised and launched into operation from 1st April 1956. No new Plan was prepared for Kerala, only some financial adjustments were effected by setting off a sum of Rs. 4.00 crores as the share of the southern Taluks of Trivandrum District and adding a sum of Rs. 19.00 crores for the Malabar area, which was added to Travancore-Cochin from Madras.
Planning Department